Superconductivity and Kondo Effect of PdxBi2Se3 Whiskers at Low Temperatures - A.A.В Druzhinin; N.S.В Liakh-Kaguy; I.P.В Ostrovskii; Yu.M.В Khoverko; K.В Rogacki (Журнал нано- та електронної фізики)
Temperature dependencies of Bi2Se3 whiskersвЂ™ resistance with Pd doping concentration of (1-2)В п‚ґВ 1019В cmВ в€’В 3 where measured in temperature range 1.5-77В K. At temperature 5.3В K a sharp drop in the whisker resistance was found. The effect observed is likely resulted from the whiskers partial transition in superconducting state at temperature 5.3В K, which is likely connected with пЃў-PdBi2 inclusions in the whiskers. Transverse magnetoresistance in n-type Bi2Se3 whiskers with different doping concentration in the vicinity to the metal-insulator transition from metal side of the transition was studied in magnetic field 0-10В T. The magnetic field suppression of superconductivity allows to determine the main parameters: upper critical magnetic field Bc2В пЂЅВ 1.5В T, superconductor coherence length пЃё(0)В пЂЅВ 15В nm, superconductive gap пЃ„В пЃѕВ 0.8В meV. Besides on the temperature dependence of the whisker resistance and magnetoresistance a minimum was observed in the temperature range 20-25В K that is connected with appearance of Kondo effect.